The Two Formyl Peptide Receptors Differently Regulate GPR84-Mediated Neutrophil NADPH Oxidase Activity - Jonas Mårtensson; Martina Sundqvist; Asmita Manandhar; Loukas Ieremias; Linjie Zhang; Trond Ulven; Xin Xie; Lena Björkman; Huamei Forsman (Karger Publishers, 2021)
Neutrophils express the two formyl peptide receptors (FPR1 and FPR2) and the medium-chain fatty acid receptor GPR84. The FPRs are known to define a hierarchy among neutrophil G protein-coupled receptors (GPCRs), that is, the activated FPRs can either suppress or amplify GPCR responses. In this study, we investigated the position of GPR84 in the FPR-defined hierarchy regarding the activation of neutrophil nicotine adenine dinucleotide phosphate (NADPH) oxidase, an enzyme system designed to generate reactive oxygen species (ROS), which are important regulators in cell signaling and immune regulation. When resting neutrophils were activated by GPR84 agonists, a modest ROS release was induced. However, vast amounts of ROS were induced by these GPR84 agonists in FPR2-desensitized neutrophils, and the response was inhibited not only by a GPR84-specific antagonist but also by an FPR2-specific antagonist. This suggests that the amplified GPR84 agonist response is achieved through a reactivation of desensitized FPR2s. In addition, the GPR84-mediated FPR2 reactivation was independent of β-arrestin recruitment and sensitive to a protein phosphatase inhibitor. In contrast to FPR2-desensitized cells, FPR1 desensitization primarily resulted in a suppressed GPR84 agonist-induced ROS response, indicating a receptor hierarchical desensitization of GPR84 by FPR1-generated signals. In summary, our data show that the two FPRs in human neutrophils control the NADPH oxidase activity with concomitant ROS production by communicating with GPR84 through different mechanisms. While FPR1 desensitizes GPR84 and by that suppresses the release of ROS induced by GPR84 agonists, amplified ROS release is achieved by GPR84 agonists through reactivation of the desensitized FPR2.